The Student SOM Survey 1994 - SOM Institute, University of Gothenburg (University of Gothenburg, 1995)
This is the second study in the collection of Student-SOM surveys. The aim of these studies is to shed light on opinions and habits of the student generation of today. The questionnaire was divided into seven parts: mass media; politics and society; energy, nuclear power and environment; Sweden and the rest of the world; leisure-time activities; background; and study programme. It was mainly a replication of the questionnaire used in Student-SOM 1993. Additional questions dealt with the respondent´s opinion on newspapers publishing names in connection with crimes and accidents; Sweden´s future relation to the European Union; and the rights of various ethnical groups to look after their interests. For a number of various things like porno movies in television, flogging, mosques, homosexual teachers, etc. the respondents had to state if they were of the opinion that it should be allowed or not. The question about choice of political party was put in two different versions; half of the respondents were asked about the probability that they should vote for a particular political party during their lifetime, and the rest were asked about the probability that they should vote for a particular political party at the 1998 general election.

Purpose:

To find out how students feel about their education and the social environment at the University of Gothenburg

Detta är den andra undersökning som SOM-institutet vid Göteborgs universitet genomför för att fånga upp åsikter och vanor hos dagens studentgeneration. Frågeformuläret som i huvudsak är en replikation av 1993 års formulär indelades i massmedia; politik och samhälle; energi, kärnkraft och miljö; Sveriges förhållande till omvärlden; fritidsintressen; bakgrund; samt kurs/linje. Frågor som tillkommit behandlade tidningars namnpublicering i samband med brott och olyckor, Sveriges framtida förhållande till EU och olika etniska gruppers rätt att ta tillvara sina egna intressen. Respondenterna fick även ange om de ansåg pornografiska filmer i TV, aga, moskéer, homosexuella lärare etc. bör vara tillåtet eller ej i Sverige. Frågan om partival ställdes i två olika versioner, halva urvalet fick frågan om sannolikheten att man kommer att rösta på ett parti under ens livstid, medan den andra hälften fick frågan om sannolikheten att man kommer att rösta för de olika partierna vid 1998 års val.

Syfte:

Ta reda på hur studenterna uppfattar sin utbildning och den studiesociala miljön vid Göteborgs universitet
SOM-undersökningen till studenter 1994
Student-SOM 1994
Keywords: CORS; CORS; Higher and further education; Gymnasial och högre utbildning; Media; Media; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap